MANAJEMEN DAN ADMINISTRASI PENDIDIKAN DASAR STUDI DI SEKOLAH DASAR NEGERI KANGGRAKSAN KOTA CIREBON - Mega Rif’atul Amalia; Mardiah Hapsah; Moh Izuddin; Muhammad Hasbi Sabari; Tamsik Udin (STKIP Subang, 2025)
This study aims to analyze the implementation of educational management and administration at SDN Kanggraksan, Cirebon City, as well as to identify the challenges encountered and the solutions developed in managing the school. Using a descriptive qualitative approach through interviews, observations, and document analysis, the study reveals that management and administration operate as complementary functions. Educational management covers strategic aspects such as planning, organizing, directing, and controlling school resources, while administration focuses on operational tasks including recording, documentation, reporting, and daily technical coordination. However, the implementation still faces several obstacles, including budget instability caused by sudden program changes, limited facilities that force the school to implement a learning shift system, inconsistent staff discipline, and a high administrative workload for teachers. To address these issues, the school employs rapid responses, collective decisionmaking, collaborative communication with stakeholders, humanistic approaches for handling HR issues, and continuous evaluation. The findings indicate that the effectiveness of school governance depends on the integration of strategic management and operational administration supported by strong collaboration among school members. This study highlights the importance of strengthening managerial and administrative systems to improve the quality, efficiency, and sustainability of primary education services.